Gambaran Tingkat Nyeri Pada Pasien Pasca Operasi Sectio Caesarea Dengan Teknik Anestesi Spinal di Bangsal Rumah Sakit Umum Daerah dr. R. Goeteng Taroenadibrata Purbalingga - Radetyo, Septiadi Putra; Yudono, Danang Tri; Yanti, Linda (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Pain after caesarean section surgery is one of the problems that often affects patients. This study aims to describe the level of pain in patients after caesarean section surgery using spinal anesthesia techniques in the ward of the Regional General Hospital, dr. R. Goeteng Taroenadibrata Purbalingga. The research method used is descriptive qualitative with a cross-sectional approach. Data were collected on post-caesarean section patients who met the inclusion criteria during the study period. Pain levels were measured using the Numeric Rating Scale (NRS) pain scale at intervals of 2 hours and 5 hours after caesarean section surgery. The results of research on 25 patients after caesarean section surgery using spinal anesthesia technique with respondents who experienced pain levels 2 hours after caesarean section surgery were 14 patients (56%) experiencing severe pain. Then, for the pain level 5 hours after caesarean section surgery, 13 patients (52%) experienced mild pain. The conclusion of the study showed that, for 2 hours after caesarean section surgery using spinal anesthesia technique in the ward of the Regional General Hospital, dr. R. Goeteng Taroenadibrata Purbalingga, 14 patients felt severe pain (56%). Meanwhile, the results of research on patient pain levels for 5 hours were 13 patients (52%) experiencing mild pain.